Analisis Kualitas Pelatihan Pegawai Pada Kantor Camat Menyuke - Naiyun Untung Utama; Dewi Rahayu Miyanti (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2020)
This study aims to find out how the quality of employee training at the Sub-district Head Office. The research method that the author uses in this research is survey research conducted in large and small populations, but the data studied is data from samples taken from the population, so that relative events, distribution and relationships between sociological and psychological variables are found. The population in this study were all of the Sub-District Head of Suke Officers. In this study the author will use a sample of 32 respondents who are employees of the Subdistrict Head of Suke. Based on the results of the analysis, obtained a total average score of 15.59 with an overall average value of 3.12 So, based on the above calculation it can be said that the quality factors of employee training at the Sub-district Office of Menyuke fall into the GOOD category, with a score 3.12 is in the range 2.50 - 3.24.